Precursor assisted crystallization in cross-linked isotactic polypropylene. (10th October 2019) - Ju, Jianzhu; Tian, Nan; Wang, Zhen; Su, Fengmei; Yang, Haoran; Chang, Jiarui; Li, Xueyu; Ali, Sarmad; Lin, Yuanfei; Li, Liangbin
Abstract: Combining the extension rheometry and simultaneous in-situ synchrotron radiation small/wide angle X-ray scattering (SAXS/WAXS) measurement, extension induced crystallization of cross-linked isotactic polypropylene (CL-iPP) is studied at different temperature from 130 to 160 °C. After extension at strain of 1.5, precursor is generated before crystallization and the relative stability increases with temperature. Precursor growth is confined due to limited chain diffusion, resulting in a periodic two-dimensional distribution. Crystallization takes place later with the existence of precursor, accompanied with the slowdown of precursor dynamics. Based on the results, a model of precursor assisted crystallization is proposed to illustrate this unique phase behavior. Graphical abstract: Image 1 Highlights: Flow induced precursor with long lifetime is observed in extended cross-linked iPP. The model of precursor assisted crystallization is proposed based on the results. Daughter lamellar with high self-similarity can be observed under SAXS.